Nursing students' perception: Escape Room use in teaching leadership skills - Chennyfer Dobbins Abi Rached; Emili Amani Alves da Cruz; Maria Helena Cardoso da Mota; Caroline da Silva Fonseca Paulo; Giovanna Micucci Pires Amaral; Daniela Lika Nakajima (Associação Brasileira de Enfermagem, 2024)
ABSTRACT Objectives: to understand nursing students' perception regarding Escape Room use to develop leadership skills. Methods: a qualitative exploratory-descriptive study, with 97 nursing students. Escape Room game sessions were held, totaling ten. Subsequently, a debriefing and analysis was carried out using the Discourse of the Collective Subject method, through the focus group technique. Ethical procedures were respected. Results: students' perceptions about using this methodology to develop leadership skills were positive and significant. The effectiveness of the game in teaching and developing these skills in nursing practice stands out. Final Considerations: the game was an effective active methodology in approaching the proposed content, promoting satisfaction and easy assimilation.